Phenomenology of Buying and Selling Practices in Islamic Societies: How is it Implemented - Mulyani, Ridha; Sulastri, Widia; Nailurrahmi, Nailurrahmi; Pratiwi, Nila; Rahmita, Rahmita; Habib, Abdul; Sihombing, Yusuf (Samara: Journal of Islamic Law and Family Studies, 2023)
Buying and selling is exchanging something you want for something equivalent through certain useful methods. The exchange must be beneficial for humans so that carcasses, liquor and blood are not included in things that may be traded or exchanged, because these objects are not useful for Muslims. According to Article 20 paragraph 2 of the Compilation of Sharia Economic Law, this research uses library research, collecting books and writings that are directly or directly related to the issues above. After the data is collected, classification analysis is then carried out using deductive methods to reach conclusions. Ba'i is buying and selling between objects and objects, or the exchange of objects for money. Primitive society when money was not used as a means of exchanging goods, namely with a barter system. Even though buying and selling using the barter system has been abandoned, and replaced by a currency system, sometimes the essence of such buying and selling still applies, even if it is to determine the amount of goods exchanged but is calculated using a certain currency value, for example, Indonesia buys vehicle spare parts to Japan, then the imported goods are paid for.